Finite element simulation and experimental verification of quasi-static compression properties for 3D spacer fabric/hollow microspheres reinforced three phase composites. (28th May 2021) - Yu, Lingjie; He, Xiaoyi; Liang, Fanchao; Meng, Jiaguang; Fu, Sida; Zhi, Chao; Zhang, Yuming; Sun, Fengxin
Abstract: To enhance the compressive properties of syntactic foams, a new type of ternary composite named 3D spacer fabric/hollow microspheres reinforced composite (3DSMRC) was designed by adding warp-knitted space fabric (WKSF) into traditional syntactic foam. In order deeply understand the meso-mechanical properties of 3DSMRC composites, the compression tests of 3DSMRC were carried out and the quasi-static compression finite element models were established based on COMSOL Multiphysics. The results show that the compression properties of 3DSMRC were obviously controlled by structures of WKSF. To be specific, the 3DSMRC composites with more spacer yarns per unit area could withstand higher critical load, and with denser surface layers and larger spacer yarns inclination-angle could gain better compression capacities. Meanwhile, different types of microspheres also had important impact on the compression capacities of specimens, which could be improved by using smaller radius ratio (higher strength) microspheres. In addition, the finite element model can accurately reproduce the compression process and stress-strain curves of representative 3DSMRC samples, and then accurately simulate the values of compressive modulus and yield strength. The simulation and experimental studies of 3DSMRC can help to obtain a better and deeper understanding of the compression properties of this new type of composite, and finally provide a useful theoretical reference for the optimization design of 3DSMRC.